2014
DOI: 10.1177/0146167214536741
|View full text |Cite
|
Sign up to set email alerts
|

Honor and the Stigma of Mental Healthcare

Abstract: Most prior research on cultures of honor has focused on interpersonal aggression. The present studies examined the novel hypothesis that honor-culture ideology enhances the stigmatization of mental health needs and inhibits the use of mental health services. Study 1 demonstrated that people who strongly endorsed honor-related beliefs and values were especially concerned that seeking help for mental health needs would indicate personal weakness and would harm their reputations. Studies 2 and 3 showed that honor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
56
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(65 citation statements)
references
References 31 publications
5
56
0
Order By: Relevance
“…Research has observed high rates of violence in subcultures with strong culturally-sanctioned beliefs related to “honor” and “respect”. Such “honor cultures” have been documented among Caucasians in the American South (Brown, Imura, & Mayeux, 2014), and a similar construct has been described among highly disenfranchised youth in inner city African-American neighborhoods (Anderson, 1999). In communities with high rates of violence, failure to respond aggressively to provocation or “disrespect” may invite further victimization and thus retaliation is seen as a means of reducing future threat (Stewart & Simons, 2010).…”
Section: Discussionmentioning
confidence: 72%
“…Research has observed high rates of violence in subcultures with strong culturally-sanctioned beliefs related to “honor” and “respect”. Such “honor cultures” have been documented among Caucasians in the American South (Brown, Imura, & Mayeux, 2014), and a similar construct has been described among highly disenfranchised youth in inner city African-American neighborhoods (Anderson, 1999). In communities with high rates of violence, failure to respond aggressively to provocation or “disrespect” may invite further victimization and thus retaliation is seen as a means of reducing future threat (Stewart & Simons, 2010).…”
Section: Discussionmentioning
confidence: 72%
“…Men must instead acquire a tough reputation, demonstrating their ability to respond to insults and to use violence to defend their property, 'their' women and their family (Barnes, Brown, & Osterman, 2012;Barnes, Brown, & Tamborski, 2012;Brown, Imura & Mayeux, 2014;Brown, Osterman, & Barnes, 2009).…”
Section: Cultural Honourmentioning
confidence: 99%
“…There are many barriers in LMICs in the implementation of successful anti-stigma programs: these include low rates of psychiatric help seeking (that may be influenced by common cultural beliefs about traditional medicine), domestic violence, gender dynamics (i.e., “Machismo” or “Culture of Honor” within certain cultural groups) (27), lack of political prioritization of mental health care, low financial investment on health, and material poverty and social marginalization (10). …”
Section: Lessons From Developing Countriesmentioning
confidence: 99%